Improving the Quality of Early Childhood Education with the Role of Parents in the Digital Era - Sari, Diah Ayu Puspita; Suraijiah, Suraijiah; Hidayati, Sari (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
The purpose of this study is to improve the quality of preschool children's education through the role of parents in the digital world. The research method used is qualitative, using data collection methods such as observation, interviews and literature research. The results show that active participation of parents in monitoring and accompanying their children in the use of technology is an important step in improving the quality of education. Involved parents can guide the use of technology for learning and support children's cognitive, social and emotional development. In addition, this study shows the importance of collaboration between parents and educational institutions to effectively utilize technology to promote children's development. The conclusion of this study shows that parental support for the smart and responsible use of technology can optimize infant development and prevent the negative impact of technology on children. This research is expected to contribute to the development of digital education and guide parents in facing the challenges of the digital era.